2015
DOI: 10.3892/ol.2015.3082
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of quintuple primary cancer, including esophageal cancer: A case report

Abstract: Abstract. The present study reports the rare case of a patient with quintuple primary cancer that underwent systematic treatment, including surgical intervention. A 63-year-old male patient was initially diagnosed with primary esophageal cancer and hypopharyngeal cancer. The patient underwent total pharyngolaryngoesophagectomy using a thoracoscopic method and reconstruction using the free jejunal flap and gastric tube and was subsequently administered adjuvant chemotherapy (80 mg/m 2 intravenously on day 1, ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…[2,3] Combined with other facts such as the advancement of early detection techniques, surgical procedures, and perioperative adjuvant therapies, the number of long-term cancer survivors continues to increase, which has resulted in an increased incidence of SPMs in patients with esophageal cancer. Previous studies have shown that 4.0% to 37.4% of esophageal cancer survivors developed a SPM during their follow-up period, [411] which will result in an even heavier burden related to the survival of patients with esophageal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…[2,3] Combined with other facts such as the advancement of early detection techniques, surgical procedures, and perioperative adjuvant therapies, the number of long-term cancer survivors continues to increase, which has resulted in an increased incidence of SPMs in patients with esophageal cancer. Previous studies have shown that 4.0% to 37.4% of esophageal cancer survivors developed a SPM during their follow-up period, [411] which will result in an even heavier burden related to the survival of patients with esophageal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study reported that the number of second malignancies accounted for ~16% of all cases registered in 2003 based on the Surveillance Epidemiology and End Results (SEER) database (11). Also, Otowa et al demonstrated that approximately 36.2% of ECs were observed with multiple primary cancers (12). However, the risk factors related to second cancer differ between SCC and AC and have not been discussed separately (13,14).…”
mentioning
confidence: 99%